Unfair risk allocation in oil and gas upstream service contracts in Malaysia: the necessity for Oilfield Anti-indemnity Act - Wan Zahari, Wan Mohd Zulhafiz; Abdul Rahman, Nasarudin (Universiti Malaysia Sarawak, 2020)
In Malaysia, the absence of a law to regulate imbalanced risk allocation and unfair indemnity and hold harmless clauses in oil and gas service contracts should be perceived as a serious problem. Such deficiency leads to the problem of inequality of bargaining power resulting from the dominant position of the operators over the contractors. Moreover, to date, there is no statutory restriction on contractual provisions purporting to exclude, limit or indemnify one or both of the parties in relation to liability and indemnity. Some operators opt to take out self-insurance rather than to buy a premium that will extend its coverage to cover the operators and sub-contractors, for example in respect of Construction All Risk. This scenario can cause the contractor to assume uninsured risks, which could lead to detrimental financial exposure on the occasion of a catastrophic incident. The situation might get worse for contractors in the event that contractors have to assume double jeopardy contractual risk, whereby the contractors not only need to assume operators’ risk but also sub-contractors’ risk. In order to resolve this problem, it is argued that a specific legal mechanism should be adopted in Malaysia to protect and limit the liability of the contractors under oil and gas service contracts. It is suggested that the Malaysian Parliament should pass a special law, such as, Oilfield Anti-Indemnity Act. It would be ideal and practical solution to have a proper legal framework to control the abuse of imbalanced risk allocation and indemnity and hold harmless clauses in Malaysia. The methodology employed in this paper will be a comparative analysis which will be carried out in a descriptive, analytic and prescriptive manner.